2022
DOI: 10.3389/fpls.2022.957336
|View full text |Cite
|
Sign up to set email alerts
|

Maize and peanut intercropping improves the nitrogen accumulation and yield per plant of maize by promoting the secretion of flavonoids and abundance of Bradyrhizobium in rhizosphere

Abstract: Belowground interactions mediated by root exudates are critical for the productivity and efficiency of intercropping systems. Herein, we investigated the process of microbial community assembly in maize, peanuts, and shared rhizosphere soil as well as their regulatory mechanisms on root exudates under different planting patterns by combining metabolomic and metagenomic analyses. The results showed that the yield of intercropped maize increased significantly by 21.05% (2020) and 52.81% (2021), while the yield o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 77 publications
1
8
1
Order By: Relevance
“…Furthermore, we found Azotobacter , a typical plant beneficial non-symbiotic nitrogen-fixing bacterial genus, to be cross-enriched from peanut to maize, possibly also contributing to improved nitrogen nutrition in maize. Our results are in line with previous findings on microbiota-dependent improvement of nitrogen nutrition 31 , 32 , 34 36 . Overall, legume/gramineae combinations are promising candidates for intercropping and are therefore the subject of intensive research in soil science and plant nutrition.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, we found Azotobacter , a typical plant beneficial non-symbiotic nitrogen-fixing bacterial genus, to be cross-enriched from peanut to maize, possibly also contributing to improved nitrogen nutrition in maize. Our results are in line with previous findings on microbiota-dependent improvement of nitrogen nutrition 31 , 32 , 34 36 . Overall, legume/gramineae combinations are promising candidates for intercropping and are therefore the subject of intensive research in soil science and plant nutrition.…”
Section: Discussionsupporting
confidence: 93%
“…Maize and peanut could engage in a ‘giving-receiving feedback’ interaction through the convergence of their microbiomes in intercropping. Peanut plants are legumes and host nitrogen-fixing bacteria in their root nodules 31 , such that peanut could improve nitrogen acquisition of maize 27 , 32 . We indeed found evidence for this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The potential role of plant root exudates has been verified by many researchers ( Baetz and Martinoia, 2014 ), which includes the effect of root exudates on plants themselves ( Li et al., 2019 ), on other plants ( Dong et al., 2022 ), on microorganisms and even on soil ecosystems ( Tian et al., 2021 ). In this study, it was found that maize root exudates inhibited the seed germination of radish, cucumber, lettuce, pepper, and ryegrass, and AMF colonization alleviated the inhibition of maize root exudates on the seed germination of the above recipient plants.…”
Section: Discussionmentioning
confidence: 95%
“…We observed that M. verticalis larvae-feeding significantly enriched Bradyrhizobium (bacterial genus) and Talaromyces (fungal genus), and the relative abundance of Bradyrhizobium and Talaromyces gradually increased with the elevation of the larvae density. Notably, Bradyrhizobium is one of the most cosmopolitan and diverse bacterial group modulating a variety of host legumes, which can promote growth, increase yield, and improve abiotic stresses resistance [ 47 , 48 ] in various plants, including rice [ 49 ] peanuts [ 50 ], and maize [ 51 ]. In addition, Talaromyces can promote plant growth and inhibit pathogenic fungi and insects [ 52 – 54 ], such as Talaromyces apiculatus reduced linear mycelial growth of Ganoderma boninense , elevated area and bole girth of oil-palm seedlings, and increased shoot and root biomass, and nutrient contents in seedlings [ 52 ].…”
Section: Discussionmentioning
confidence: 99%